Scientific websites for children: Nurturing children's scientific literacy through the conflation of multiple semiotic resources. Issue 3 (1st October 2020) - Diani, Giuliana; Sezzi, Annalisa
Abstract: Nowadays, knowledge dissemination among children is no longer limited to the classroom and course or information books. It also includes websites explicitly addressed to youngsters who have a different stage of cognitive development and background knowledge compared to adults. However, they are also the first to live in today's multimodal hypertext environment and have a multimodal and multimedial communicative competence. In web-based educational hypermedia, education and entertainment often converge, relying on different semiotic resources. In point of fact, the term 'edutainment' is frequently used to describe such a combination. Edutainment websites are also one of the main accesses to science for children. In particular, explanations of scientific phenomena are frequently intertwined with different kinds of visual material, partly evoking science books. The aim of this paper is to shed light on the verbal-visual interplay in three scientific websites designed for children in English, whose express aim is to popularize scientific knowledge.